Dose deposits from 90Y, 177Lu, 111In, and 161Tb in micrometastases of various sizes: Implications for radiopharmaceutical therapy - Hindie, Elif (2016)
Radiopharmaceutical therapy, traditionally limited to refractory metastatic cancer, is being increasingly used at earlier stages, such as for treating minimal residual disease. The aim of this study was to compare the effectiveness of90Y,177Lu,111In, and161Tb at irradiating micrometastases.90Y and177Lu are widely used β--emitting radionuclides.161Tb is a medium-energy β-radionuclide that is similar to177Lu but emits a higher percentage of conversion and Auger electrons.111In emits -photons and conversion and Auger electrons. Methods: We used the Monte Carlo code CELLDOSE to assess electron doses from a uniform distribution of90Y,177Lu,111In, or161Tb in spheres with diameters ranging from 10 mm to 10 m. Because these isotopes differ in electron energy per decay, the doses were compared assuming that 1 MeV was released per m3, which would result in 160 Gy if totally absorbed. Results: In a 10-mm sphere, the doses delivered by90Y,177Lu,111In, and161Tb were 96.5, 152, 153, and 152 Gy, respectively. The doses decreased along with the decrease in sphere size, and more abruptly so for90Y. In a 100- m metastasis, the dose delivered by90Y was only 1.36 Gy, compared with 24.5 Gy for177Lu, 38.9 Gy for111In, and 44.5 Gy for161Tb. In cell-sized spheres, the dose delivered by111In and161Tb was higher than that of177Lu. For instance, in a 10- m cell,177Lu delivered 3.92 Gy, compared with 22.8 Gy for111In and 14.1 Gy for161Tb. Conclusion:177Lu,111In, and161Tb might be more appropriate than90Y for treating minimal residual disease.161Tb is a promising radionuclide because it combines the advantages of a medium-energy β-emission with those of Auger electrons and emits fewer photons than111In. 2016 by the Society of Nuclear Medicine and Molecular Imaging, Inc.